Objetos que circulam: perspectivas da cultura material para o estudo da feira da marreta em Goiânia (GO) - Rosa, Mana Marques (2023)
The following research is based on studies that focus on the “social life” of objects, their trajectories and “cultural biographies”, seeking to move towards an “anthropology of objects” or an “anthropology of things”. This ethnography presents and analyzes a cultural biography of Feira da Marreta (Marreta’s Flea Market), which happens in Goiânia (GO) city, seeking to understand its historical and cultural aspects concerning value, negotiation and exchange of material objects. This objective is unfolded and developed through the observation of objects’ paths, circulation, ambiguities and singularities in face of the intricate relationships human beings create with them inside specific cultures. Objects were once produced, became commodities and were tossed away, but they are brought back to the circuit of economic exchange inside the so-called “second hand” markets, thus enabling a “second life” of things, similarly to what happens with cultural goods in patrimonialization and musealization processes. To understand this circulation is what allows us to observe processes that affect objects by creating value, defunctionalization, and new interpretations and meanings in different contexts. Therefore, this research is an effort (1) to analyze the circulation, exchange and value of material objects in Feira da Marreta (Marreta’s Flea Market); (2) to create the trajectories of the objects exchanged inside this market, using ethnography, and understanding defunctionalization, interpretations and new meanings; and (3) to consider attentively the processes of selection, “value attribution” and construction of cultural patrimony that perhaps we might be able to identify in this case study.